"무선 센서 네트워크에서 센서 노드들 사이의 메시지 암호화/복호화 방법" (Translated TITLE: Message encryption/ecryption method between sensor nodes in wireless sensor networks) - Pathan, Al-Sakib Khan; Hong, Choong Seon; Haque, Md Mokammel; Heo, Gihyuk (2010)
Korean Patent in Korean Language. Hence, the translated and Korean both DRAFT versions are uploaded. The patent was applied in 2007 and accepted in 2010. Please visit Networking Lab, KHU's website and find information with the Patent Number: 10-0941764 . http://networking.khu.ac.kr/publications/pub.htm